2000
DOI: 10.1046/j.1523-1755.2000.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac aldosterone production and ventricular remodeling

Abstract: An intracardiac production of aldosterone has been recently reported in rat. This production is increased both acutely and chronically by angiotensin II, observations suggesting that the heart contains a steroidogenic system that is regulated similarly to the adrenal one. Cardiac production of aldosterone is small compared with that of the adrenal, raising the question of its function in normal conditions. Moreover, the regulation of this synthesis in pathophysiologic states remains unknown. In an analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 37 publications
6
87
0
2
Order By: Relevance
“…Several studies have described the ability of chronic in vivo treatment with spironolactone to diminish myocardial fibrosis in response to MI. 3,4 However, the results of the present study indicate comparatively early ex vivo effects of corticosteroids to enhance tissue injury and apoptosis in response to myocardial ischemia and the ability of spironolactone to oppose these effects and maintain tissue viability.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Several studies have described the ability of chronic in vivo treatment with spironolactone to diminish myocardial fibrosis in response to MI. 3,4 However, the results of the present study indicate comparatively early ex vivo effects of corticosteroids to enhance tissue injury and apoptosis in response to myocardial ischemia and the ability of spironolactone to oppose these effects and maintain tissue viability.…”
mentioning
confidence: 54%
“…In contrast, aldosterone replacement in the face of adrenalectomy typically results in recapitulation of target-organ damage to, or even worse than, the sham-operated control condition. Although previous reports indicate significant myocardial production of aldosterone, 3 more recent studies indicate that the majority of aldosterone found in cardiac tissue is derived from the circulation 10 and is consistent with the ability of adrenalectomy to produce impressive end-organ protective effects. Studies with aldosterone synthase inhibitors further support the importance of aldosterone in target-organ damage.…”
Section: Aldosterone Synthase Inhibition: the Importance Of Aldosteronementioning
confidence: 67%
“…The observed increased myocardial aldosterone levels in patients with HCM is in accordance with the results of recent studies showing extraadrenal gland synthesis of aldosterone, including studies in cardiac myocytes and fibroblasts and the myocardium of patients with heart failure. 19,27,29,30 In the adrenal glands and cultured cells, expression of CYP11B2 is regulated by a diverse array of factors, including angiotensin II, 31 cAMP, 15 12-lipoxygenase, 32 PKC isoforms, 33,34 and calmodulin-dependent protein kinases. 35 These factors, alone or in combination, are plausible candidates to affect expression of CYP11B2 in HCM hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone may be produced in cardiomyocytes in the heart 27,28 and VSMCs, 4,29 although it is not established whether concentrations achieved are high enough to exert local effects. 30 Indeed, in the rat heart, for example, there is little evidence that aldosterone synthase (CYP11B2) and 11(␤)-hydroxylase (CYP11B1) genes are expressed, because there is either extremely low expression of mRNA or protein for steroidogenic enzymes or they are not found at all.…”
Section: Smooth Muscle Cellsmentioning
confidence: 99%